Pengembangan Kompetensi Guru dalam Menghadapi Era Revolusi Industri 4.0 - Muhamad Ibnu Soleh (Education Research Center, 2025)
The Fourth Industrial Revolution has had a significant impact on the transformation of education, including increasingly complex and dynamic demands on teachers' competencies. This study aims to systematically examine various literature related to the development of teacher competencies in responding to the challenges of the digital era. A literature review method was employed, analysing relevant scholarly sources, including journal articles, academic books, policy documents, and reports from international organisations published between 2015 and 2025. The findings indicate that teachers are required to possess digital literacy skills, critical thinking, creativity, collaboration, and the ability to integrate technology into student-centred learning practices. Furthermore, continuous professional development, institutional support, and a shift in mindset are key factors in strengthening teachers' capacity in the era of the Fourth Industrial Revolution. This study recommends the need for policies that support needs-based training, professional collaboration, and equitable provision of digital infrastructure. Thus, the findings of this research can serve as a foundation for policymaking and educational practices that are more responsive to the demands of the times.